Socio-demographic Characteristics of Acute Appendicitis Patients attended at a Tertiary Care Teaching Hospital in Bangladesh (Bangladesh Journal of Infectious Diseases, 2020)
Background: Acute appendicitis can cause morbidity in a large number of people.Objective: The purpose of the present study was to see the socio-demographic characteristics of acute appendicitis patients.Methodology: This descriptive cross sectional study was conducted in the Department of Surgery at Rajshahi Medical College Hospital, Rajshahi, Bangladesh from July 2009 to June 2011 for a period of two years. Patients admitted with features of uncomplicated and complicated acute appendicitis (gangrenous or perforated) underwent emergency appendectomy by grid iron incision in all the units of surgery were selected as study population. All clinical information including history, physical findings and investigation reports were collected and recorded in a pre-designed data collection sheet.Result: A total number of 200 acute appendicitis patients were recruited for this study. Most of the study population were in the age group of 13 to 20 years of age group which was 84(42.0%) cases. The ratio of male and female was 1:1.04. Married were more than unmarried which was 114(57.0%) cases and 86(43.0%) cases respectively. Majority patients of this study was from middle class which was 160(80.0%) cases. Most of the acute appendicitis patients were presented with uncomplicated status which was 136(68.0%) cases and the rest 64(32.0%) cases were in complicated state.Conclusion: In conclusion most of the acute appendicitis patients are young age female coming from middle class family.Bangladesh Journal of Infectious Diseases 2019;6(2):44-47